DI-091 Colistimethate sodium prescription in the elderly: a retrospective study in one academic medical centre. (25th February 2017) - Mendes, M; de Oliveira, R Palmeira; Morgado, S; Fonseca, O
Abstract : Background: According to the assessment report of the European Medicines Agency (EMA, 2014), colistimethate sodium is considered a crucial therapeutic option in the context of infections caused by multiresistant gram negative pathogens. This report presents guidelines on dosage regimens: a daily dose of 9 MIU is suggested for adult patients and reduced doses are indicated when creatinine clearance (CrCL) is <50 mL/min. No special recommendations are given for elderly patients although it is known that renal function decreases with age and loss of muscular mass influences this biomarker. Purpose: To evaluate prescription patterns for colistimethate sodium and dosage adjustments in our hospital, particularly concerning the elderly. To analyse the accomplishment of EMA indications and the need for dosage adjustments in the elderly. Material and methods: Prescriptions over 1 year (1 August 2015 to 1 August 2016) were studied. Inclusion criteria were: patients >65 years, admitted to medicine and pulmonology services, prescribed with intravenous colistimethate sodium. Exclusion criteria were: death and transfer to another hospital during the treatment period. Results: The study population consisted of 27 patients, 62.96% being older than 80 years. From all of the studied patients, 21 presented normal (or below) creatinine (CrCL >50 mL/min). Of these 21 patients only 6 (28.57%) began treatment with 9 MUI (2 were <70 years old; the others were >80 years) and for 2 of the older group, dose reduction occurred within treatment. The remaining 15 patients (aged >70 years) had other therapeutic regimens: 12 patients were prescribed 6 MIU/day, 8 older than 80 years, and 2 needed further dose reduction. For the 6 patients with renal impairment before treatment, a reduced dose of antibiotic was prescribed. However, only 2 were prescribed the daily dose in accordance with the guidelines. Conclusion: These data call attention to the need to consider the limitations of creatinine as a sole biomarker of renal function in the elderly. Further studies in large populations could provide useful data to enrich the guidelines on dosage adjustment of colisthimetate sodium in this population. References and/or acknowledgements: European Medicines Agency. European Medicines Agency completes review of polymyxin-based medicines. Available at: http://www.ema.europa.eu/docs/en_GB/document_library/Press_release/2014/10/WC500176334.pdf ; 2014. (accessed: 1 October 2016). No conflict of interest